Do cultural factors alter the relationship between risk attitudes and economic welfare? - Huong Dien Pham (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2017)
This paper analyzes how cultural factors shape risk attitudes and subsequently alter its relationship with economic welfare. The research sample is comprised by a three wave balanced panel data set of 588 ethnically diverse households collected between 2008 and 2013 in the Central Vietnam. Different ethnic groups are characterized by different languages, customs and beliefs that create the cultural diversity of the sample. Different approaches are used to examine the relationship between risk attitudes and economic welfare in the presence of the cultural diversity. First, a single-equation estimation method using a fixed effects model and a Hausman-Taylor model is employed to examine the unidirectional relationship. Second, a simultaneous equation estimation method using the Three Stage Least Squares model is applied to explore a bidirectional relationship between risk attitudes and economic welfare. Among the ethnic minorities, results indicate a negative association between willingness to take risks and economic welfare at low degree but a positive at the higher degree of risk-taking. For the ethnic majority, a positive and mutual relationship between risk attitudes and economic welfare is indicated. The ethnic majority is economically better-off than their minority counterparts are, whereas the minorities are economically homogenous but strongly diverse in risk attitudes and social factors. This study sheds light on the cultural heterogeneity in the individual risk attitudes as well as in shaping its relationship with economic welfare. Generally, it is suggested to consider sociocultural factors via risk-taking channel in socioeconomic policies that target ethnically or culturally diverse populations. Particularly, that implies a need to encourage the risk-taking strategies among the extremely risk-averse individuals, particularly who belong to the ethnic minorities.
Keywords: C33; D81; I30; R20; Z19; 330; Ethnicity; Risk attitude; Economic welfare; Simultaneous equation model